Iocma 2023 2023
DOI: 10.3390/iocma2023-14409
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Machine Learning Methods—SVR, XGBoost, LSTM, and MLP— For Forecasting the Moroccan Stock Market

Hassan Oukhouya,
Khalid El Himdi

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Using LSTM models in stock market forecasting enables the effective capture of long-term dependencies, resulting in precise predictions. The LSTM cell operates based on four equations, which govern its underlying principle [11]:…”
Section: Lstm Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Using LSTM models in stock market forecasting enables the effective capture of long-term dependencies, resulting in precise predictions. The LSTM cell operates based on four equations, which govern its underlying principle [11]:…”
Section: Lstm Modelmentioning
confidence: 99%
“…Results showed that this approach outperformed the baseline ARIMA model regarding Mean Squared Error (MSE), Root-Mean-Square Error (RMSE), and Mean Absolute Error (MAE) on a Forex dataset from 2008-2018. In a comparative conducted by Oukhouya and El Himdi [11], various ML methods, including XGBoost, Support Vector Regression (SVR), Multilayer Perceptron (MLP), and LSTM, were evaluated for forecasting a daily closing price of the Morocco Stock Index 20 (MSI 20). The results demonstrated that the SVR and MLP models, optimized with Grid Search (GS), have outperformed other models and achieved outstanding accuracy in price prediction.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, this work focuses on more comprehensive feature selection and hybrid algorithm composition. Oukhouya and El Himdi [15] explored the use of various machine learning methods like SVR, XGBoost, MLP, and LSTM to forecast daily prices of the MSI 20 index. But our research stands out because it combines feature selection and regression algorithms to enhance stock price prediction.…”
Section: Introductionmentioning
confidence: 99%
“…In stock market prediction, various time-series methodologies, including Long Short-Term Memory (LSTM)-based models, have been employed to develop predictive frameworks [5]. Although LSTM models have proven their worth across numerous sequence learning tasks, their global modeling approach, which relies on the entirety of the training data, may sometimes overlook subtle nuances within certain feature space areas.…”
Section: Introductionmentioning
confidence: 99%